Stalking Perpetration in Adolescents in the Context of Intimate Partner Violence - Gomes, Marta (Victims & offenders, 2024)
Intimate partner violence can occur as a form of stalking behaviour, which is considered a pattern of repeated and unwanted behaviours towards another individual. A cross-sectional study was conducted with 498 participants from Portugal, aged between 12–21 years. Findings support that adolescent stalking perpetrators exhibited psychopathic traits, psychopathology, aggression, and childhood trauma. Results showed that anxiety partially mediates the association between childhood trauma and stalking perpetration. These findings provide a better understanding of stalking in adolescence, which allows professionals to have a more comprehensive approach when considering intervention programs. Limitations and future research are discussed.